Metabolic Adaptations During Staphylococcus aureus and Candida albicans Co-Infection - Eichelberger, Kara R.; Cassat, James E. (Frontiers in Immunology, 2021)
Successful pathogens require metabolic flexibility to adapt to diverse host niches. The presence of co-infecting or commensal microorganisms at a given infection site can further influence the metabolic processes required for a pathogen to cause disease. The Gram-positive bacterium Staphylococcus aureus and the polymorphic fungus Candida albicans are microorganisms that asymptomatically colonize healthy individuals but can also cause superficial infections or severe invasive disease. Due to many shared host niches, S. aureus and C. albicans are frequently co-isolated from mixed fungal-bacterial infections. S. aureus and C. albicans co-infection alters microbial metabolism relative to infection with either organism alone. Metabolic changes during co-infection regulate virulence, such as enhancing toxin production in S. aureus or contributing to morphogenesis and cell wall remodeling in C. albicans. C. albicans and S. aureus also form polymicrobial biofilms, which have greater biomass and reduced susceptibility to anti-microbials relative to mono-microbial biofilms. The S. aureus and C. albicans metabolic programs induced during co-infection impact interactions with host immune cells, resulting in greater microbial survival and immune evasion. Conversely, innate immune cell sensing of S. aureus and C. albicans triggers metabolic changes in the host cells that result in an altered immune response to secondary infections. In this review article, we discuss the metabolic programs that govern host-pathogen interactions during S. aureus and C. albicans co-infection. Understanding C. albicans-S. aureus interactions may highlight more general principles of how polymicrobial interactions, particularly fungal-bacterial interactions, shape the outcome of infectious disease. We focus on how co-infection alters microbial metabolism to enhance virulence and how infection-induced changes to host cell metabolism can impact a secondary infection.